The truncated isoform of the receptor for hyaluronan-mediated motility (RHAMMΔ163) modulates shelterin and telomerase reverse transcriptase transcription affecting telomerase activity - Basu, Kaustuv (Frontiers in Aging, 2025)
IntroductionThe receptor for hyaluronan-mediated motility (RHAMM), a centrosomal protein expressing in multiple isoforms, is implicated in telomerase-independent aging. However, its involvement in telomerase regulation is unproven. This study aims to investigate whether RHAMM correlates with telomerase activity in mammalian cells.MethodsMouse embryonic fibroblasts expressing or lacking full-length RHAMM (RHAMMFL, amino acids 1–794) and the shorter isoform RHAMMΔ163 (amino acids 164–794), were explored to examine the effect of RHAMM isoforms on mRNA expression of telomerase reverse transcriptase (TERT) and selective shelterin proteins regulating telomere maintenance.ResultsThe preliminary findings revealed that RHAMM regulated Tert expression based on its isoforms. RHAMMΔ163 enhanced Tert mRNA expression and promoted telomerase activity by stimulating sirtuin 1 (Sirt1), shelterin proteins Tpp1, and Pot1a and repressing the telomerase inhibitor Pinx1 levels. In contrast, RHAMMFL did not have significant effect on TERT expression and telomerase activity. Increasing Tert mRNA expression by blocking leucine zipper sequence with function-blocking RHAMM peptide NP-110 in a TERT-deficient mouse model of idiopathic pulmonary fibrosis, alongside suppressing Tpp1 and Pot1a expression in mouse embryonic fibroblasts using ERK1 inhibitor PD98059, highlights the importance of the HATABD domain (amino acids 718–751), which includes leucine zipper and ERK-binding sequences at the C-terminus of mouse RHAMM in regulating telomerase function. Increased telomerase activity raised Hmmr expression, suggesting a potential feedback loop between RHAMM and TERT expression.DiscussionTaken together, this report provides the first evidence that RHAMMΔ163 regulates TERT and shelterin expression and telomerase activity in mammalian cells.